2020
DOI: 10.3389/fpsyt.2020.00664
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Bacterial Overgrowth and Irritable Bowel Syndrome – An Update

Abstract: Small intestinal bacterial overgrowth (SIBO) is one manifestation of gut microbiome dysbiosis and is highly prevalent in IBS (Irritable Bowel Syndrome). SIBO can be diagnosed either by a small bowel aspirate culture showing ≥10 3 colony-forming units (CFU) per mL of aspirate, or a positive hydrogen lactulose or glucose breath test. Numerous pathogenic organisms have been shown to be increased in subjects with SIBO and IBS, including but not limited to Enterococcus, Escherichia coli, and Klebsiella. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 99 publications
2
96
0
15
Order By: Relevance
“…Intestinal damage or dysbiosis could contribute to malabsorption and, although organic diseases such as celiac disease and inflammatory bowel disease were ruled out, participants were not investigated for other conditions, such as small-intestinal bacterial overgrowth (SIBO) [ 38 ]. A large meta-analysis of 25 case-control studies concluded prevalence of the condition in as many as 31% of IBS patients [ 38 ]. Dietary manipulation could affect the microbiota and improve SIBO [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal damage or dysbiosis could contribute to malabsorption and, although organic diseases such as celiac disease and inflammatory bowel disease were ruled out, participants were not investigated for other conditions, such as small-intestinal bacterial overgrowth (SIBO) [ 38 ]. A large meta-analysis of 25 case-control studies concluded prevalence of the condition in as many as 31% of IBS patients [ 38 ]. Dietary manipulation could affect the microbiota and improve SIBO [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large meta-analysis of 25 case-control studies concluded prevalence of the condition in as many as 31% of IBS patients [ 38 ]. Dietary manipulation could affect the microbiota and improve SIBO [ 38 , 39 ]. A previous report demonstrated that dietary interventions for specific, malabsorbed carbohydrates influenced the composition of the gut microbiota [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that intestinal microbiota disorders may promote the development and deterioration of the symptoms of irritable bowel syndrome, 24 and intestinal microbiota may affect the two-way communication between the enteric nervous system and central nervous system. 25 Previous studies have demonstrated that immune system activation and proinflammatory cytokines may indirectly affect skin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dysbiosis is often observed in a variety of intestinal disorders including IBS [ 17 , 35 , 37 ]. For example, the small intestinal bacterial overgrowth (SIBO), characterized by the overgrowth of colonic type bacteria, such as Klebsiella, Enterococcus , and Escherichia , is frequently observed in the small intestine of IBS patients [ 38 , 39 ]. SIBO can potentially induce increased gut permeability, low grade inflammation, dysmotility, and decreased absorption of bile salts, and also alter enteric nervous system (ENS) activity [ 38 ].…”
Section: Role Of Intestinal Resident Microbiota In Ibs Pathologymentioning
confidence: 99%